On distribution of migratory fry of pink salmon in the stream of a small Sakhalin river - Alexander M. Kaev; Yury I. Ignatyev (Известия ТИНРО, 2015)
Distribution of migratory fry of pink salmon Oncorhynchus gorbuscha in the stream of the Voznesenka River (south-eastern Sakhalin) is investigated and its high inhomogeneity is revealed. One of the reasons is the stream structure - the fry aggregate mainly in the main flow. Another reason could be the fry behavior - they instinctively try to form aggregations with visual contact, in particular in relatively light nights or in conditions of their high abundance (short distance between the individuals).